Variability analysis in judo para athletes with visual impairments: match-outcome performance in the Tokyo 2020 Paralympic Games with evidence from the new classification system - Kons, R. L.; Dos Santos, D. F. C.; Carvalho, R.; da Silva, A. F.; Lopes-Silva, J. P.; Franchini, E.; Detanico, D. (Adapted Physical Activity Quarterly, 2024)
Match-related performance analysis in judo Para athletes with visual impairments is important to coaches and staff to identify technical-tactical profiles of their athletes and opponents but also to identify whether there are similar characteristics in each visual class. Thus, this study explores the match-related performance in judo Para athletes and verifies the relationship between performance using the old and new classification systems. The match-derived variables were analyzed using different statistical methods considering a total of 182 matches from the Tokyo 2020 Paralympic Games. The results indicated that performance was affected by sex and degree of impairment. The new classification system seems suitable for grouping Para judo athletes, as it differentiates performance between the two proposed classes (J1 and J2), since athletes from each group compete separately. Furthermore, different variability index measures were correlated with competitive performance, demonstrating a specific performance profile for each sport class in judo.